Guilotes, a new genus of Coelotinae spiders from Guangxi Zhuang Autonomous Region, China (Araneae, Agelenidae) - Bing Li; Zhe Zhao; Haifeng Chen; Zhiyan Wu; Chuntian Zhang; Shuqiang Li (ZooKeys, 2018)
A new genus of the subfamily Coelotinae F.O. Pickard-Cambridge, 1893, Guilotes Z. Zhao & S. Li, gen. n. from China is described, as well as four new species: G. ludiensis Z. Zhao & S. Li, sp. n. (♂♀, type species), G. qingshitanensis Z. Zhao & S. Li, sp. n. (♂♀), G. xingpingensis Z. Zhao & S. Li, sp. n. (♂♀) and G. yandongensis Z. Zhao & S. Li, sp. n. (♀). The DNA barcodes of all species are documented for future use.